Controlled release of imatinib mesylate from PLGA microspheres inhibit craniopharyngioma mediated angiogenesis - (:unkn) unknown (SPRINGER, 2013)
Poly(lactic-co-glycolic acid) microspheres loaded with imatinib mesylate has been developed as a new therapeutic strategy to prevent craniopharyngioma recurrence. Microspheres composed of different lactic/glycolic acid ratios, molecular weights and drug compositions were synthesized and loaded with imatinib mesylate by modified double-emulsion/solvent evaporation technique and subsequently characterized by particle-size distribution, scanning electron microscopy, encapsulation efficiency and in vitro drug release. Inhibitory potential of imatinib containing microspheres on tumor neovascularization was investigated on craniopharyngioma tumor samples by rat cornea angiogenesis assay. Results showed that microspheres in different LA:GA ratios [LA:GA 50:50 (G50), 75:25 (G25), 85:15 (G15)] considerably reduced neovascularization induced by recurrent tumor samples in an in vivo angiogenesis assay (P < 0.01). Our data indicate that local delivery of imatinib mesylate to the post-surgical tumoral cavity using biodegradable microspheres may be a promising biologically selective approach to prevent the recurrence of craniopharyngiomas, via inhibition of neovascularization.
Keywords: DELIVERY-SYSTEMS; GROWTH-FACTOR; MALIGNANT GLIOMAS; DRUG-DELIVERY; ASSAYS; EXPERIENCE; PROTEINS